The Effectiveness of Video Games for Learning and Teaching English Language Among School-Age Students - Putra, Alfaro Electra Bimantara (CV. Akademi Merdeka, 2025)
This study discusses the effectiveness of video games in learning and teaching English to young learners through an extensive review of literature and meta-analysis on published research papers from 2009 to 2025. The results reveal the effectiveness of video games in promoting vocabulary, communicative, and confidence domains, with gamers performing better in language games in comparison to non-gamers. There was, however, little to no difference in formal academic achievement, English GPA. The effectiveness of learning through video games depends on the genre, with narrative-based video games proven to be an essential element in vocabulary development and multiplayer video games in speech development. The implications of this research indicate that video games, if properly integrated into structured digital game-based language learning platforms, can act as an additional teaching supplement.